Portal hypertension & cirrhosis - John Wiley & Sons, Ltd; Zhonghua yi xue hui (China : 1949- ) (John Wiley & Sons Ltd. Limited, 2022)
A peer-reviewed journal that aims to publish cutting edige academic advances on innovative achievements and practice in the field of portal hypertension and cirrhosis.
Keywords: Portal hypertension; Portal hypertension : Research; Liver : Cirrhosis; Liver : Cirrhosis : Treatment